THINKING WITH THE INSTITUTIONAL BYPASS? - Cohen, Amy J. (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2020)
Sometimes the most promising path to changing an entrenched system is to maneuver around it. Or so argue law and development scholars Mariana Mota Prado and Michael J. Trebilcock who develop the idea of an institutional bypass—an alternative pathway to perform some function or service provided badly by the state. With the institutional bypass, Prado and Trebilcock advance an approach to reform that is incremental, modest, dynamic, contextual, and revisable. And they advance an approach to political governance that favors regulatory competition, decentralization, and flexibility. Through richly descriptive case study analyses, Prado and Trebilcock also illuminate the differential material consequences of specific institutional bypasses—they recommend the bypass’s procedural features if they work on the ground in the eyes of their users.